1976
DOI: 10.1039/f19767200382
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion, viscosity and sedimentation of poly(ethylene oxide) in water

Abstract: Results are reported for measurements of the diffusion coefficients of poly(ethy1ene oxide) fractions in aqueous solution and of the viscosities and sedimentation coefficients at temperatures between 8 and 35"C, for molecular weights from 1000 to 6000. These show that the polymers behave in water as non-free-draining coiled molecules having dimensions which become less perturbed by the solvent as the temperature is lowered, the &temperature is estimated at 5°C. The unperturbed dimensions are seen to decrease w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…X‐ray structural analysis has shown that crystalline PEG chains can adopt two extreme structural conformations: a zigzag, random coil structure for shorter chains, or a winding, helical structure for longer chains 49. It has been argued from earlier studies that viscosity50–53 and diffusion coefficient data50 support a random coil conformation, whereas it has been claimed from calorimetric data54 that it adopts a helical conformation. Based on volumetric studies, Lepori and Mollica32 favour a compromise model for PEG in solution is a hydrated flexible coiled polymer with some helical segments.…”
Section: Resultsmentioning
confidence: 99%
“…X‐ray structural analysis has shown that crystalline PEG chains can adopt two extreme structural conformations: a zigzag, random coil structure for shorter chains, or a winding, helical structure for longer chains 49. It has been argued from earlier studies that viscosity50–53 and diffusion coefficient data50 support a random coil conformation, whereas it has been claimed from calorimetric data54 that it adopts a helical conformation. Based on volumetric studies, Lepori and Mollica32 favour a compromise model for PEG in solution is a hydrated flexible coiled polymer with some helical segments.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing temperature decreases the magnitude of both the excess partial molar enthalpy and entropy of PEG in solution (Figure 7), and suggests that the structure of the hydration shell around the PEG gradually disappears as the temperature is raised. That is, the decrease in magnitude of the partial molar entropy of PEG in solution as temperature increases can be attributed to the increase in the free rotation of chain links and weakening of the polymersolvent interactions in solution (Chew and Couper, 1976). On the other hand, increasing temperature does not significantly change either the excess partial molar enthalpy or entropy of DEX (Figure 8).…”
Section: Discussionmentioning
confidence: 97%
“…This result can be compared with the end to end distance calculated from where C ∞ is the so-called characteristic ratio, which is a measure of the effect of short-range interactions within a chain, n is the number of bonds, and l is the average C−C bond length of 0.146 nm in PEO and PPO . For PEO in water, C ∞ (PEO) ≅ 5 …”
Section: Discussionmentioning
confidence: 99%
“…46 For PEO in water, C ∞ (PEO) = 5. 51 Experimental values of C ∞ (PPO) for PPO in water are not available since PPO is not water soluble. However, in various polar solvents C ∞ (PPO) = C ∞ (PEO).…”
Section: Discussionmentioning
confidence: 99%